Infrared spectrum and intermolecular potential energy surface of the CO–O2 dimer. Issue 21 (21st May 2018) - Barclay, A. J.; McKellar, A. R. W.; Moazzen-Ahmadi, N.; Dawes, Richard; Wang, Xiao-Gang; Carrington, Tucker
Abstract : The spectrum of the weakly-bound radical complex CO–O2 is studied for the first time. Abstract : Only a few weakly-bound complexes containing the O2 molecule have been characterized by high resolution spectroscopy, no doubt due to the complications added by the oxygen molecule's unpaired electron spin. Here we report an extensive infrared spectrum of CO–O2, observed in the CO fundamental band region using a tunable quantum cascade laser to probe a pulsed supersonic jet expansion. The rotational energy level pattern derived from the spectrum consists of stacks of levels characterized by the total angular momentum, J, and its projection on the intermolecular axis, K . Five such stacks are observed in the ground vibrational state, and ten in the excited state ( ν (CO) = 1). They are divided into two groups, with no observed transitions between groups. The groups correspond to different projections of the O2 electron spin, and correlate with the two lowest fine structure states of O2, ( N, J ) = (1, 0) and (1, 2). The rotational constant of the lowest K = 0 stack implies an effective intermolecular separation of 3.82 Å, but this should be interpreted with caution since it ignores possible effects of electron spin. A new high-level 4-dimensional potential energy surface is developed for CO–O2, and rotational energy levels are calculated for this surface, ignoring electron spin. By comparing calculated and observed levels, it is possible to assign detailed quantum labels to the observed level stacks.